Estimation of Sexual Dimorphism of the Mandible in Coastal Karnataka and Kerala Populations using Cone Beam Computed Tomography - Rao, Kumuda; Shetty, Mahabalesh; Nayak, U. S. Krishna; Babu, G. Subhas; Shetty, D. Prashanth; Shetty, Prajwal K. (Journal of Health and Allied Sciences NU, 2021)
Objective The mandible has been used for sex determination and forensic identification due to its unique anatomy and morphology. Every part of the mandible is unique, including the shape and size of the temperomandibular joint, the ramus, the body and the symphysis region, and the inferior alveolar canal. In addition, the position and placement of the teeth within their sockets are unique for every individual.Sample Population A study was conducted on 20 males and females to estimate sexual dimorphism using anthropometric measurements obtained by cone beam computed tomography images of the mandible of Karnataka and Kerala populations.Materials and Methods The mean, standard deviation, and standard error along with the confidence interval of different measurements were documented. Various measurements between the sexes were compared using Student's t-test. Association between categorical variables was analyzed using the Chi-square test. A p-value < 0.05 was considered to be statistically significant. Data were analyzed using statistical SPSS software.Results The p-value of mRBr L, GA L, and GA R among females was significantly higher in the Karnataka population when compared with that in the Kerala population. The Karnataka State population showed significantly higher values of RL R, BiGBr, and BiCBr among males, and the p-value of the Kerala population for GGL L and GGL R was significant and higher among the males.Conclusion The data derived from the above study suggest that the mandibular anthropometric measurements used may be applied for forensic sex estimation.
Keywords: sexual dimorphism; forensic facial reconstruction; morphometric measurements; cone beam computed tomography; mandible